The Response of Contemporary Indonesian Islamic Parties Toward Pluralism - Firman Noor (Journal of Indonesian Social Sciences and Humanities, 2017)
Religion-based political parties, particularly Islamic parties, are often perceived as being less committed in comparison to secular parties in preserving pluralism. Some people regard them to have hidden agendas which are not proper for Indonesia as a plural country. By exploring the ideals and practical aspects of several main Islamic parties, this article wants to show the nature of Islamic parties’ views and attitudes in answering political diversity that in the long run indicates the real position of this party in pluralism in politics. To measure Islamic parties’ commitment on pluralism, this article would explore some issues namely (1) the main purpose of party establishment, (2) concept on the ideal form and foundation of a state, including the vision on Pancasila (3) attitudes towards minority groups, including the non-Muslims, Ahmadiyah, Syiah and any other minority group (4) policies related to religious concerns, including rights to have religious education, Islamic Syariah establishment at the local level, and radicalism, (5) compliance to develop political cooperation with secular and non-Muslim parties. The discussion will also touch upon the reason behind the response towards pluralism as well as addressing the question on whether the response towards pluralism is based on pragmatic interests or Islamic idealism. Discussion on this response of the Islamic parties will also reveal the gradation and level of commitment of the Islamic Parties to pluralism, which in general tend to be supportive towards pluralism.